THE ROLE OF TEACHERS IN SHAPING STUDENTS' CRITICAL THINKING SKILLS. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The role of teachers in shaping students’ critical thinking skills is profoundly significant in the modern educational landscape. As the demands of the twenty-first century continue to evolve, the necessity for students to become not only repositories of knowledge but also critical thinkers and problem-solvers has become clear. Critical thinking skills enable students to analyze information objectively, evaluate complex issues, and make well-reasoned decisions, which are crucial capabilities for thriving in a rapidly changing world. In this context, teachers are not merely transmitters of factual information; rather, they serve as guides, facilitators, and motivators who actively encourage the development of students’ abilities to think critically and independently.